Analysis of the Level of Tourist Satisfaction with the Quality of Tourism Information Center Services at Yogyakarta International Airport - Oktavia Eka Putri Wibowo; Yunus Purnama (CV. Rayyan Dwi Bharata, 2024)
Tourism is an industry that is growing rapidly. Tourism has an important role in encouraging economic activity, improving the country's image, improving community welfare, and providing expanded employment opportunities. In an effort to increase tourism, the Tourism Information Center is presented as a tourism-oriented information center that provides detailed information about a destination. The tourism industry as a service industry has the main characteristic, namely service, therefore service plays a very important role. This research aims to analyze the level of satisfaction of service users with service quality using the Customer Satisfaction Index (CSI) method at the Tourism Information Center at Yogyakarta International Airport. This research uses a quantitative type of research using descriptive methods. Data collection was carried out by distributing questionnaires to visitors to the Tourism Information Center at Yogyakarta International Airport. The population in this study are visitors who have received services from the Tourism Information Center at Yogyakarta International Airport at least once. The sampling method used was Non Probability Sampling with Purposive Sampling technique. Based on the research results, service users were very satisfied with the service performance provided by the Tourism Information Center. This can be seen from the CSI value obtained, which is 94.2%. Things that need to be improved or improved in the Tourism Information Center service, one of which is the availability of physical facilities such as brochures, maps, and others with a fairly large gap between interest and satisfaction.